Serum Biomarkers are Promising Tools to Predict Traumatic Brain Injury Outcome - Al-Ameri, Laith Thamer; Hameed, Ekhlas Khalid (AL-Kindy College Medical Journal, 2021)
Traumatic Brain Injury (TBI) is still considered a worldwide leading cause of mortality and morbidity. Within the last decades, different modalities were used to assess severity and outcome including Glasgow Coma Scale (GCS), imaging modalities, and even genetic polymorphism, however, determining the prognosis of TBI victims is still challenging requiring the emerging of more accurate and more applicable tools to surrogate other old modalities